The Revised Supervisory Architecture under the Markets in Crypto-Assets Regulation: The Next Step in the Evolution of the EU Financial Sector - Stanchev, Dimitar (Teisė, 2025)
In May 2023, the European financial sector underwent a significant change, notably with the adoption of the Markets in Crypto-Assets Regulation (MiCAR), making the EU the first major jurisdiction to regulate crypto-assets. The Regulation aims to boost competitiveness and innovation in the financial industry, potentially positioning the Union as a global leader in crypto-asset standards.The study highlights that, beyond its immediate impact, MiCAR marks a major step in enhancing the Union’s financial supervision structure since the creation of the European System of Financial Supervision back in 2010. Based on its key division of crypto-assets into significant and ‘non-significant’ (a classification-based supervisory model), MiCAR expands the role of the European Supervisory Authorities, especially the European Banking Authority (EBA). For the first time, the EBA is given direct supervisory powers, including the competence to establish and chair certain advisory structures.The article concludes that this development represents a considerable shift in the EU approach to financial supervision and is likely to raise many practical challenges, particularly in managing the relations between supervised entities and the EBA. The change requires a thorough analysis due to its long-term implications.